The heterogeneity of lipoproteins and their role in the development of cardiovascular diseases - E. A. Utkina; O. I. Afanasieva; S. N. Pokrovsky (Российский кардиологический журнал, 2019)
The lipid hypothesis of atherosclerosis pathogenesis is based on lipid metabolism disorders and, in particular, hypercholesterolemia. The main participants of dyslipidemia are lipoproteins of various classes. Despite the use of modern lipidlowering drugs, the residual risk of cardiovascular complications in patients with dyslipidemia remains quite high. Modern biochemical and physico-chemical methods allowed demonstrating the high heterogeneity of the main classes of lipoproteins.This review presents the analysis of modern ideas about the heterogeneity of lipoproteins, a brief description of existing approaches to the classification of lipoproteins, methods of their stratification, as well as the contribution of some subfractions of lipoproteins to the development of atherosclerosis.